Dysfunctional uterine bleeding - Ludmir Grimberg, Abraham (2015)
On the issue itself, there are a number of controversies in the definition and nomenclature, and so, as in synonymy is called dysfunctional uterine bleeding, hemorrhagic Metropatía, abnormal uterine bleeding, functional bleeding, etc., etc. In our semantics, the term Dysfunctional would be most appropriate.